2021
DOI: 10.1016/j.toxrep.2021.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of silver nanoparticle-induced sexual behavior and testicular parameters dysfunction in male mice by yttrium oxide nanoparticles

Abstract: Graphical abstract Alleviation of silver nanoparticle-induced sexual behavior and testicular parameters dysfunction in male mice by yttrium oxide nanoparticles. Gasem Mohammad Abu-Taweel, Hani Manssor Albetran, Mohsen Ghaleb Al-Mutary, Mohammad Ahmad, It Meng Low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…YO-NPs have been demonstrated to be a powerful element that can be applied for many biomedicine purposes [ 49 ]. We noted in our previous experiment that YO-NPs moderated the toxic effects of Ag-NPs on testicular function by improving oxidative parameters and decreasing apoptotic cells [ 50 ]. Schubert et al [ 51 ] mentioned the ability of the YO-NPs to protect nerve cells from oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…YO-NPs have been demonstrated to be a powerful element that can be applied for many biomedicine purposes [ 49 ]. We noted in our previous experiment that YO-NPs moderated the toxic effects of Ag-NPs on testicular function by improving oxidative parameters and decreasing apoptotic cells [ 50 ]. Schubert et al [ 51 ] mentioned the ability of the YO-NPs to protect nerve cells from oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…MDA content in ELISA methods can be used to detect lipid peroxidation, which is one of the main indicators of oxidative stress (77,81,89). With commercial kits, GSH levels and total antioxidant capacities can be measured, as well as analyzed at the level of antioxidant biomolecules and enzymes such as CAT, SOD (83, 91,133).…”
Section: Experimental Methods For Assessing the Kesmentioning
confidence: 99%
“…In our database, the most reported of the biological events is Ag NPs exposure triggering oxidative stress, which is described in 22 out of the 48 articles at both cellular and tissue level. It has been shown that accumulation of Ag NPs depleted cells from the molecular antioxidant GSH (39,(75)(76)(77), and decreased super oxide dismutase (SOD) and catalase (CAT) activities (29,39,(77)(78)(79), altered enzymatic oxidative defense system in male reproductive system (29,38,39,77,80,81) and lead to increased ROS levels in human sperm (82), in mouse Sertoli cells (15P-1) (83), in somatic Leydig (TM3) and Sertoli (TM4) cells (36,84) which eventually cause oxidative stress. In addition, mitochondrial damage due to the impairment of metallothionein (MIE) would result in oxidative stress by inhibition of electron transfer chain enzymes and perturbation of antioxidant system.…”
Section: Identi Cation and Selection Of Key Eventsmentioning
confidence: 99%
See 2 more Smart Citations